Automated tracheal intubation in an airway manikin using a robotic endoscope: a proof of concept study. (3rd January 2020) - Biro, P.; Hofmann, P.; Gage, D.; Boehler, Q.; Chautems, C.; Braun, J.; Spahn, D. R.; Nelson, B. J.
Summary: Robotic endoscope‐automated via laryngeal imaging for tracheal intubation (REALITI) has been developed to enable automated tracheal intubation. This proof‐of‐concept study using a convenience sample of participants, comprised of trained anaesthetists and lay participants with no medical training, assessed the performance of a robotic device for the insertion of a tracheal tube into a manikin. A prototype robotic endoscope device was inserted into the trachea of an airway manikin by seven anaesthetists and seven participants with no medical training. Each individual performed six device insertions into the trachea in manual mode and six in automated mode. The anaesthetists succeeded with 40/42 (95%) manual insertions (median (IQR [range]) 17 (12–26 [4–132]) s) and 40/42 (95%) automated insertions (15 (13–18 [7–25]) s). The non‐trained participants succeeded in 41/42 (98%) manual insertions (median (IQR [range]) 18 (13–21 [8–133]) s) and 42/42 (100%) automated insertions (16 (13–23 [10–58])] s). The duration of insertion did not differ between groups. An effect of increasing experience was observed in both groups in manual mode. A Likert scale for 'ease of use' (0 = very difficult to 10 = very easy) showed similar results within the two groups; the mean (SD) was 5.9 (2.1) for the anaesthetists and 6.9 (1.3) for the non‐trained participants. We have successfully performed the first automated tracheal device insertion in a manikin with comparable results in a convenience sample of anaesthetists and lay participants with no medical training.